Icariin Inhibits AMPK-Dependent Autophagy and Adipogenesis in Adipocytes In vitro and in a Model of Graves' Orbitopathy In vivo - Li, Hong; Yuan, Yifei; Zhang, Yali; Zhang, Xia; Gao, Long; Xu, Rongjuan (Frontiers in Physiology, 2017)
Graves’ orbitopathy (GO), an extrathyroidal manifestation of Graves’ disease, is an inflammatory autoimmune disorder of the orbit that involves the differentiation of precursor cells into mature adipocytes and retro-orbital adipose tissue accumulation. Here, we examined the involvement of autophagy in adipogenesis and explored the effects of icariin, a flavonoid isolated from the genus Epimedium with a wide range of biological and pharmacological effects, on autophagy and adipogenesis in 3T3-L1 preadipocytes and in a mouse model of GO. Microscopic examination of autophagosome formation and lipid droplet accumulation by Oil Red O staining, and western blot assessment of autophagic markers in the presence of the autophagy inhibitors Asn and 3-MA showed that autophagy is necessary for adipogenesis. Icariin inhibited the differentiation of preadipocytes into mature adipocytes by suppressing autophagy, and these effects were mediated by the inhibition of AMPK/mTOR pathway activation. In a mouse model of thyroid stimulating hormone receptor induced GO, icariin reduced orbital muscle adipose tissue expansion and lipid droplet accumulation by inhibiting AMPK/mTOR mediated autophagy. Collectively, these results reveal a potential mechanism underlying the protective effects of icariin against autophagy induced adipogenesis and suggest that icariin could be developed as a new therapeutic candidate for the prevention and treatment of GO.